PENCARIAN RUTE TERPENDEK MENGGUNAKAN ALGORITMA DIJKSTRA PADA SISTEM INFORMASI GEOGRAFIS PEMETAAN STASIUN PENGISIAN BAHAN BAKAR UMUM - Berry Junanda; Denny Kurniadi; Yasdinul Huda (Universitas Negeri Padang, 2016)
The capital city of West Sumatera, Padang, had so many event to increase its tourism. Every year, the domestic tourist coming and passing by to Padang, increasing the consumption of fuel in Padang. However, the information about location of gas station in Padang is not easy-to access. The focus of this project is to provide the information about location of gas station in Padang. This project aims to help people to find track between gas station. The systems are designed with a web-based map layers represented by MapServer. The data (maps) was made with ArcGIS and MapInfo, digitized into shapefile form (vector model), the track finder using Dijkstra’s Algorithm. As well as general contained in the database storage system using the application postresql and PostGIS, implemented into web pages via PHP. This outcomes of this project is a geographic information system that provides general information of gas station in Padang. Visitors can find the location based on the name of the gas station. Then the system provide the track between gas station and track from the point that visitor decide. General information will be displayed in tabular form and location information is displayed in the form of maps showing the location of the point. Keywords: Geograpic Information System, Algorithm, Dijkstra, MapServer, OpenLayer, PostgreSQL/PostGis.